A new needle nematode, Longidorus maginicus n. sp. (Nematoda: Longidoridae) from southern Spain. (9th June 2022) - Liébanas, G.; Clavero-Camacho, I.; Cantalapiedra-Navarrete, C.; Guerrero, P.; Palomares-Rius, J.E.; Castillo, P.; Archidona-Yuste, A.
Abstract: During nematode surveys in natural vegetation in Sierra Mágina, Jaén province, southern Spain, a Longidorus species closely resembling Longidorus carpetanensis was found, but application of integrative taxonomic approaches clearly demonstrated that it is a new species described herein as Longidorus maginicus n. sp. The new species is amphimictic, characterized by a moderately long body (4.2–5.2 mm); lip region anteriorly flattened, slightly separated from the rest of body by a depression, 9.0–11.0 μm wide and 3.5–6.0 μm high; amphidial fovea not lobed; relatively short odontostyle (61.0–70.5 μm); guiding ring located 23.5–27.0 μm from anterior end; vulva located at 42.0%–51.3% of body length; female tail 39.0–61.0 μm long, conoid, dorsally convex with rounded terminus ( c ′ = 1.3–2.1), with two or three pairs of caudal pores; and males common (1:2 ratio males:females), with moderately long spicules (39.0–48.5 μm) and 1 + 6–9 ventromedian supplements and three juvenile developmental stages. According to the polytomous key, codes for the new species are (codes in parentheses are exceptions): A2-B1-C2-D2-E1-F2(3)-G2-H5(4)-I2-J1-K6. The results of molecular analysis of D2–D3 28S, internal transcribed spacer region, partial 18S rDNA, and cytochrome oxidase c subunit 1 ( coxI ) gene sequences further characterized the new species status, and separated it from L. carpetanensis and other related species.